National face to face training course on utilizing the Excel CLEANED tool for assessing the environmental impact of animal production - Masmoudi, Ahlem (Deutsche Gesellschaft für Internationale Zusammenarbeit, 2024)
The photo shows a group of 33 participants (64% women) engaged in practical exercises during CLEANED tool training course. The participants come from various organizations, including OEP, DGPA, INAT, ICARDA, and GIZ.